Evaluation of Prescribing Pattern of Drugs in Hemodialysis Patients - Reshma Begum (International Journal of Antibiotics, 2024)
Background: Patients undergoing hemodialysis often exhibit a high level of dependency and frequently present with multiple co-morbid conditions Chronic kidney disease (CKD) poses a significant global public health challenge, with its association with numerous complications. Prescribing medications appropriately for individuals with CKD presents a substantial challenge. Objective: The study aimed to assess the prescribing patterns of drugs in hemodialysis patients. Results: Out of the total 82 selected patients, 42 (51%) were male, and 40 (49%) were female. The prescribed drugs for dialysis patients included cardiovascular drugs (73.14%), gastrointestinal drugs (90.23%), antidiabetics (52.86%), hematopoietic agents (82.92%), vitamins and minerals (68.27%), and antibiotics (63.92%). Conclusion: The study's conclusion indicates that individuals undergoing dialysis predominantly consisted of elderly patients with concurrent co-morbid conditions. The prescribed medications for dialysis patients primarily included cardiovascular drugs, gastrointestinal drugs, antidiabetics, hematopoietic agents, vitamins and minerals, as well as antibiotics.
Keywords: Chronic kidney disease; Co morbid conditions; ESRD; Prescription patterns; hemodialysis